OP0037 Denosumab discontinuation and associated fracture incidence: Analysis from the freedom trial. (23rd January 2014) - Törring, O.; Brown, J.; Jensen, J.-E.B.; Gilchrist, N.; Recknor, C.; Roux, C.; Austin, M.; Wang, A.; Grauer, A.; Ho, P.-R.; Wagman, R.
Abstract : Background: In the FREEDOM pivotal phase 3 fracture trial, denosumab 60 mg every 6 months decreased the risk of new vertebral, nonvertebral and hip fractures at 3 years versus placebo. 1 As osteoporosis is a chronic disease, continued treatment is required to provide antifracture efficacy. Discontinuation of denosumab is associated with transient increases in bone remodelling and declines in bone mineral density (BMD), 2, 3 but the effect on fracture risk is not as well characterized. Objectives: To understand fracture incidence in an osteoporotic population after cessation of denosumab treatment. Methods: We evaluated subjects in FREEDOM who received 2–5 doses of investigational product (IP), either denosumab or placebo, and discontinued treatment while continuing study participation for ≥6 months since the last dose + 1-month study visit window (≥7 months). The off-treatment observation period began 7 months after last IP dose and lasted approximately 6–24 months (for subjects who received 5 to 2 doses, respectively). Results: Among subjects eligible for this analysis, age, prevalent fracture, and lumbar spine and total hip BMD T-scores were similar at baseline in placebo (N=470) and denosumab groups (N=327). During the treatment period, more subjects treated with placebo than denosumab sustained a fracture (19% vs 11%) and had significant decreases in BMD (17% vs 1%). Alternative therapy after last IP dose was initiated by 42% of placebo-treated vs 28% of denosumab-treated subjects. After treatment cessation, similar percentages of subjects in both groups sustained a new fracture (9% placebo, 7% denosumab), resulting in a fracture rate/100 subject-years of 13.5 and 9.7, respectively (Hazard Ratio 0.82; 95% Confidence Iinterval: 0.49, 1.38), adjusted for age and total hip BMD T-score at baseline. Fracture occurrence during the off-treatment period was not apparently different between the treatment groups. Conclusions: This analysis indicated that there was no excess fracture risk after treatment cessation with denosumab when compared with placebo during the off-treatment period (≤24 months). References: Cummings S et al., NEJM 2009. Miller PD et al., Bone 2008. Bone HG et al., JCEM 2011 Disclosure of Interest: O. Törring Consultant for: Takeda Nycomed, Amgen, Speakers Bureau: Takeda Nycomed, Amgen, J. Brown Grant/Research support from: Abbott, Amgen, Bristol-Myers Squibb, Eli Lilly, Merck, Novartis, Pfizer, Roche, sanofi-aventis, Servier and Warner Chilcott, Consultant for: Amgen, Eli Lilly, Merck, Novartis, sanofi-aventis, Warner Chilcott, Speakers Bureau: Amgen, Eli Lilly, Novartis, J.-E. B. Jensen Consultant for: Eli Lilly, Takeda Nycomed, Amgen, Novartis, MSD, Speakers Bureau: Eli Lilly, Takeda Nycomed, Amgen, Novartis, MSD, N. Gilchrist Grant/Research support from: Merck Sharpe & Dohme, Amgen, Consultant for: Eli Lilly, Merck Sharpe & Dohme, Amgen, Speakers Bureau: Eli Lilly, Merck Sharpe & Dohme, Amgen, C. Recknor Consultant for: Zelos, Takeda, Dramatic Health, Novartis, Eli Lilly, Paid Instructor for: Amgen, Novartis, Publicis Meetings, C. Roux Grant/Research support from: Amgen, Novartis, Consultant for: Amgen, Novartis, MSD, M. Austin Shareholder of: Amgen, Employee of: Amgen, A. Wang Shareholder of: Amgen, Employee of: Amgen, A. Grauer Shareholder of: Amgen, Employee of: Amgen, P.-R. Ho Shareholder of: Amgen, Employee of: Amgen, R. Wagman Shareholder of: Amgen, Employee of: Amgen